Further records of burrow-associated palaemonid shrimps (Decapoda: Palaemonidae) - Anker, Arthur; de Grave, Sammy (Zootaxa, 2019)
Despite the ubiquitous nature of symbiosis in palaemonid shrimps (Caridea: Palaemonidae) which live in or on varied invertebrate hosts, such as echinoderms, sponges, ascidians, hard and soft corals, etc., very few taxa have been recorded living in burrows constructed by other animals. This is in sharp contrast to the rich burrow-dwelling diversity in the Alpheidae, in which numerous genera associate with a great variety of burrowing animals, including stomatopods (Hayashi 2002; Ďuriš & Anker 2014), echiurans (Anker et al. 2005, 2015), other alpheid shrimps (e.g. De Grave 2004; Anker & Marin 2006), and especially numerous ghost and mud shrimps (e.g. Anker, 2011; Anker & Lazarus 2015).